Crimes against Financial Interests of the European Union in Poland: A Legal and Criminological Analysis of the Phenomenon - Jerzy GĄSIOROWSKI (Communications of International Proceedings, 2021)
The objective of the article is to present the status of Polish crimes against financial interests of the European Union, which may help implement the process of fighting the system of financial frauds by Polish and international law enforcement authorities in that regard. The indicated purpose was achieved with the use of an analysis of legal acts regulating said issue, an analysis of subject literature, as well as official statistical data reflecting the status of this criminality and the modes of operation of perpetrators who swindle resources originating from the budget of the European Union.
Keywords: Financial Fraud; Fraud; Criminality; Mode of Operation; European Union